Antifreeze Protein Improves the Cryopreservation Efficiency of Hosta capitata by Regulating the Genes Involved in the Low-Temperature Tolerance Mechanism - Phyo Phyo Win Pe; Aung Htay Naing; Chang Kil Kim; Kyeung Il Park (Horticulturae, 2021)
In this study, whether the addition of antifreeze protein (AFP) to a cryopreservative solution (plant vitrification solution 2 (PVS2)) is more effective in reducing freezing injuries in Hosta capitata than PVS2 alone at different cold exposure times (6, 24, and 48 h) is investigated. The upregulation of C-repeat binding factor 1 (CBF1) and dehydrin 1 (DHN1) in response to low temperature was observed in shoots. Shoots treated with distilled water (dH2O) strongly triggered gene expression 6 h after cold exposure, which was higher than those expressed in PVS2 and PVS2+AFP. However, 24 h after cold exposure, gene expressions detected in dH2O and PVS2 treatments were similar and higher than PVS2 + AFP. The expression was highest in PVS2+AFP when the exposure time was extended to 48 h. Similarly, nitric reductase activities 1 and 2 (Nia1 and Nia2) genes, which are responsible for nitric oxide production, were also upregulated in low-temperature-treated shoots, as observed for CBF1 and DHN1 expression patterns during cold exposure periods. Based on the gene expression patterns, shoots treated with PVS2+AFP were more likely to resist cold stress, which was also associated with the higher cryopreservation efficiency of PVS2+AFP compared to PVS2 alone. This finding suggests that the improvement of cryopreservation efficiency by AFP could be due to the transcriptional regulation of CBF1, DHN1, Nia1, and Nia2, which might reduce freezing injuries during cryopreservation. Thus, AFP could be potentially used as a cryoprotectant in the cryopreservation of rare and commercially important plant germplasm.